Design and In Vitro Evaluation of Gastroretentive Tablets of Doxylamine succinate - Hamad, Farah (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of the study was to prepare and evaluate a gastroretentive sustained release delivery system for doxylamine succinate, using a release-retarding polymer. The floating approach was applied for preparing gastroretentive tablets (GRT). Materials and Methods: Four GRT formulations were prepared by melting granulation technique followed by double compression. The granules were subjected to pre-compression evaluation, namely, angle of repose, loose and tapped bulk densities, Carr’s compressibility index, and Hausner’s ratio. Three of the GRT formulations were prepared using hydroxypropyl methylcellulose K4M (HPMC K4M) as a release-retarding polymer, at different concentrations. Results and Discussion: The mechanism of doxylamine released from the GRT formulations were then assessed by fitting the in vitro dissolution data obtained to zero-order, first-order, Higuchi’s, and Korsmeyer–Peppas models. It seems that formulations containing different concentrations of HPMCK4M, closely follow the first-order and Higuchi models for kinetic of drug release. Although the regression coefficients of zero-order and Korsmeyer–Peppas model for the three formulations showed relatively low values, all diffusion exponent (n) values, were above 0.5 value, which indicates that the mechanism of drug release from those formulations follow a non-Fickian release (diffusion and swelling) as expected from hydrophilic polymers like HPMC K4M. Conclusion: The use of a release-retarding polymer like HPMC K4M together with the floating-tablet technology can be applied to formulate basic drugs that have low solubility at the intestinal pH, to achieve sustained release pattern.